Factorizations of the groups $PSp_{6}(q)$ - Gentchev, Tsanko; Gentcheva, Elenka (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1994)
The following result is proved Let $G=PSp_e(q)$ and $G=AB$, where $A,B$ are proper non-Abelian simple subgroups of $G$. Then one of the following holds: (1) $q=2$ and $A\cong U_3(3), B \cong U_4(2)$; (2) $q=4$ and $A \cong J_2, B \cong U_4(4)$; (3) $q=2^n$ and $A \cong L_2(q^3), B \cong L_4(q)$ or $U_4(q)$; (4) $q=2^n>2$ and $A \cong G_2(q), B \cong PSp_4(q), L_4(q)$ or $U_4(q)$